Consumers’ willingness to pay for an increase fee in biodegradable plastic bag use in Bandar Baru Bangi, Selangor, Malaysia - Mohamed Noor, Muhamad Faizal; Matthew, Nitanan Koshy; Puan, Chong Leong (SAGE Publications, 2024)
Excessive and persistent use of plastic bags has caused severe environmental impact in many developing countries and the significance of biodegradable plastic bags as an alternative solution is uncertain. Bandar Baru Bangi, the second township in the Selangor state in Peninsular Malaysia, has also been plagued with problems of plastic bag use where plastic bags cover 56% of the household waste. Selangor has introduced a plastic bag fee of MYR 0.20 to shoppers who requested for it, albeit the effectiveness of such policy in changing consumer behavior is still unknown. The objectives of the study were to assess consumers’ plastic bags consumption behavior in Bandar Baru Bangi, and determine factors influencing their willingness to pay (WTP) for an increase fee in using biodegradable plastic bags. A questionnaire survey incorporating Contingent Valuation Method was conducted to elicit the consumers’ WTP. The results indicate that majority of the respondents (83%) requested one to three plastic bags per shopping trip. They moderately agreed that their tendency for plastic bag use was influenced by other consumers in the surrounding and highly agreed on the impact of environmental campaigns. The WTP for biodegradable plastic bags was estimated at MYR 0.43 which was influenced by their age and education level. The findings suggest there is a need to revisit the effectiveness of the policy and revise proper intervention measures to reduce plastic bag use. © The Author(s) 2024.